High incidence of common femoral DVT in critically ill Covid-19 patients - Haq, Zakia; Haidri, Fakhir Raza; Lalwani, Amit Kumar (Journal of the Pakistan Medical Association, 2023)
Objectives: To estimate the incidence and prevalence of deep venous thrombosis, and to evaluate the discriminative capacity of D-dimer in its diagnosis. Method: The prospective, observational study was conducted at the critical care unit of a tertiary care hospital in Pakistan from February to September 2021 and comprised consecutively admitted adult critically ill patients who were receiving therapeutic-dose anticoagulation therapy. All patients were screened on day one for deep venous thrombosis by colour doppler and compression ultrasonography. Patients who did not have deep venous thrombosis on the first scan were followed every 72 hours. Data was analysed using SPSS 26. Results: Of the 142 patients, 99(69.7%) were male and 43(30.3%) were female. The overall mean age was 53.20+/-13.3 years. On the first scan, 25(17.6%) patients had deep venous thrombosis. Of the remaining 117 patients, 78(68.4%) were followed every 72 hours, and 23(29.48%) of them developed deep venous thrombosis. The most common site for DVT was the common femoral vein 46(95.8%) and most deep venous thrombosis cases were unilateral 28(58.33%). D-dimer levels showed no discriminative capacity for diagnosis of deep venous thrombosis (p=0.79). There were no significant risk factors for the development of deep venous thrombosis. Conclusion: There was a high incidence and prevalence of deep venous thrombosis despite therapeutic-dose anticoagulation therapy. The most common affected site was the common femoral vein and most deep venous thrombosis were unilateral. D-dimer levels had no discriminative capacity for the diagnosis of deep venous thrombosis DVT. Key Words: DVT, Deep vein thrombosis, D-dimer, Ultrasonography, Incidence, Prevalence, DVT site, Anticoagulation, COVID-19, Critical care, IC.